2017
DOI: 10.1002/ejoc.201601483
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Coupling of Verdazyl Radicals

Abstract: Halogenated 3‐aryl‐1,5‐diisopropyl verdazyl radicals have been shown to undergo Suzuki–Miyaura coupling reactions with a variety of boronic acids to give biaryl‐substituted verdazyl derivatives in acceptable to good yields (50–90 %). The successful coupling depends on the halo substituent and the boronic acid, but most boronic acids could be coupled with the iodophenyl verdazyl radical under either ligandless conditions or in the presence of triphenylphosphine. The successful palladium‐catalyzed coupling react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Noteworthy, no trace of product could be detected by mass spectrometry after a reaction time of 8 h if the Sonogashira–Hagihara reaction was conducted using 3Br· [ 46 ] under otherwise identical conditions. This lower reactivity is in agreement with observations made earlier [ 39 , 40 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Noteworthy, no trace of product could be detected by mass spectrometry after a reaction time of 8 h if the Sonogashira–Hagihara reaction was conducted using 3Br· [ 46 ] under otherwise identical conditions. This lower reactivity is in agreement with observations made earlier [ 39 , 40 ].…”
Section: Resultssupporting
confidence: 94%
“…Important steps in the development of verdazyl chemistry have been the introduction of protocols that allow access to diversely substituted tetrazinanones, which can be converted to oxoverdazyls by oxidation [ 36 , 37 , 38 ]. Recently, Pd catalyzed cross-coupling reactions with oxoverdazyls and with saturated Kuhn verdazyls bearing a phenyl substituent in the C6-position have been reported [ 39 , 40 ]. These coupling reactions allow introducing substituents after the radical center has been synthesized and tolerate a large spectrum of functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…[46] under otherwise identical conditions. This lower reactivity is in agreement with observations made earlier [39,40].…”
Section: Introductionsupporting
confidence: 93%
“…The investigation of the physical properties was backed up by detailed structural analyses using crystallography supported by DFT structure optimizations. With respect to chemical properties, it was demonstrated that it is possible to use a Kuhn verdazyl carrying only H-atoms on C6 as substrate in Sonogashira-Hagihara cross-coupling reactions, which was previously only reported for oxo-verdazyls [39] or verdazyls carrying a bulky phenyl substituent on C6 [40]. In this way, the three different Kuhn verdazyls 3 .…”
Section: Resultsmentioning
confidence: 95%
“…A few years after Kuhn's discovery, syntheses leading to the orange 6-oxo-and 6-thioxoverdazyls were developed (Neugebauer & Fischer, 1980;Neugebauer et al, 1988). As of late, verdazyls experience renewed interest, partially as a result of the improvements concerning their syntheses, enabling the introduction of a large variety of substitution patterns (Paré et al, 2005;Bancerz et al, 2012;Matuschek et al, 2015;Le et al, 2017). Such tailor-made radicals have possible applications as fundamental building blocks in molecular magnets or in spintronic materials (Koivisto & Hicks, 2005;Train et al, 2009;Ratera & Veciana, 2012).…”
Section: Chemical Contextmentioning
confidence: 99%